2021
DOI: 10.1183/13993003.03721-2020
|View full text |Cite
|
Sign up to set email alerts
|

Nestin promotes pulmonary fibrosisviafacilitating recycling of TGF-β receptor I

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease that is characterised by aberrant proliferation of activated myofibroblasts and pathological remodelling of the extracellular matrix. Previous studies have revealed that the intermediate filament protein Nestin plays key roles in tissue regeneration and wound healing in different organs. Whether Nestin plays a critical role in the pathogenesis of IPF needs to be clarified.Nestin expression in lung tissues from bleomycin-treated mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…Previous studies have reported that the intermediate filament protein nestin plays an important role in tissue regeneration and wound healing in various organs [ 285 , 286 ]. Wang et al found that nestin expression was primarily localized to lung myofibroblasts and increased in a mouse model of pulmonary fibrosis and in patients with IPF [ 287 ]. The deficiency of nestin significantly alleviated pulmonary fibrosis in a mouse model.…”
Section: Mechanisms Of Wound Healing and Fibrosismentioning
confidence: 99%
“…Previous studies have reported that the intermediate filament protein nestin plays an important role in tissue regeneration and wound healing in various organs [ 285 , 286 ]. Wang et al found that nestin expression was primarily localized to lung myofibroblasts and increased in a mouse model of pulmonary fibrosis and in patients with IPF [ 287 ]. The deficiency of nestin significantly alleviated pulmonary fibrosis in a mouse model.…”
Section: Mechanisms Of Wound Healing and Fibrosismentioning
confidence: 99%
“…In addition, in order to further illustrate the functional significance of Nestin in MERCs, we used two Nestin-short hairpin RNAs (ShNES-1 or ShNES-2) as previously reported to specifically reduce Nestin expression in SLCs 33 , 34 (Supplementary Fig. 7a–c ).…”
Section: Resultsmentioning
confidence: 99%
“…For loss of Nestin function, retrovirus vectors (pSM2) encoding Nestin shRNA were used according to previous articles 33 , 34 . Scramble shRNA was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…It is an intermediate filament protein expressed in NSCs. 34 Also, NCAM is a cell surface glycoprotein capable of mediating cell adhesion and neurite formation. 35 The present study showed that irradiation could significantly promote the expression of neural differentiation-related genes in neuroshperes derived from DPSCs.…”
Section: Discussionmentioning
confidence: 99%